La EvaluaciÃ³n Del Retour En InterpretaciÃ³n SimultÃ¡nea Ãrabe-EspaÃ±ol: TransmisiÃ³n Del Discurso Original - Rayaa, Bachir Mahyub (European Scientific Journal, ESJ, 2017)
Many reasons have boosted the demand for Arabic-Spanish Simultaneous Interpreting (SI), among others the political and economic interdependence and the social and cultural relations between the Arab and the Spanish-speaking world, as well as the growing interest in the contemporary Arabic world for strategic and geopolitical reasons. Meetings and multilateral conferences have proliferated from the second half of the twentieth century. In addition, Arabic and Spanish are official languages at international organizations like the United Nations or the African Union, and they are present in the private international market of SI. However, research on the quality of Spanish-Arabic interpreting (AR-SP) remains limited, raising numerous questions on the evaluation and quality control of a profession that enables communication in an increasingly globalized world. This article, which is part of a wider study analyzing how users of interpreting services evaluate AR-SP SI, focuses on the analysis of two parameters: correct transmission and complete transmission of the Original Speech (OS). For this purpose, we have carried out an empirical study using a questionnaire to survey 25 users of interpreting services, asking them to observe and evaluate AR-SP SI over the course of a 30 minute conference. The data obtained reveals that the users are aware of the concept of quality regards interpreting and, despite not having access to the OS, form an opinion on interpreters and their work. Ultimately, in this article we investigate the elements that influence how users of interpreting services evaluate AR-SP interpreting and the consequences these elements have on the work of the interpreter.